Teachers Knowledge Of Inclusive Lower Primary Education In Ifako-Ijaiye Local Government Area Of Lagos State, Nigeria - Temitope Funminiyi Egbedeyi (Faculty of Teacher Training and Education, Universitas Terbuka, 2020)
Teachers play significant role in the process of implementing inclusive lower primary education, but it is important to note that inclusive education is yet to be fully implemented in Nigeria despite the numerous benefits associated to it. As one of the major implementers of inclusive lower primary, it is imperative to study teachers’ knowledge of inclusive lower primary education in Ifako-Ijaiye, as to provide empirical evidence. Descriptive survey research design was adopted with thirty five (35) teachers who were sampled using simple random. A self-designed research instrument titled Teachers Knowledge of Inclusive Education Questionnaire (? = 0.92) was used to collect data. One research question was answered and two hypotheses were tested at 0.05 level of significance. Teachers have average knowledge of inclusive lower primary education (Average Percentage = 53.6). Regular and special teachers have no significant difference on knowledge of inclusive education (t = 0.50; df = 33; p>0.05). Based on the findings, it was recommended that Nigerian Government, concerned Non-Governmental Organizations and Scholars should ensure that regular trainings are organized for lower primary teachers in order to update their knowledge about inclusive education